What makes good LMOOCs for EFL learners? Learners' personal characteristics and Information System Success Model. Issue 1 (2nd January 2023) - Hsu, Liwei
Abstract: This study presents essential findings that would be advantageous to the designers and practitioners of Language Massive Open Online Courses (LMOOCs). It reveals the key elements that contribute to successful LMOOCs, and how they are influenced by English as a foreign language (EFL) learners' personal characteristics (gender, age, and opened to experience). Nineteen research hypotheses were proposed to be statistically tested. A questionnaire, based on Delone and McLean's Information System Success Model (ISSM), included items designed to investigate EFL learners' personal characteristics, which was then distributed to experienced EFL LMOOC learners. The data from 172 valid copies (n = 172) were collected and analyzed with the administration of PLS-SEM modeling. The results reported that 9 out of 19 hypotheses were supported. It was determined that EFL learners' "openness to experience" personality trait can significantly affect their opinions of service, system, and information quality of LMOOCs. Moreover, system quality, as perceived by EFL learners, was considered the significant variable for use intention and satisfaction of LMOOCs. Use intention would lead to their increased use of LMOOCs and satisfaction, and both variables would further influence their perception of the benefits that LMOOCs may provide.